High dose genistein in Sanfilippo syndrome: A randomised controlled trial. Issue 5 (13th June 2021) - Ghosh, Arunabha; Rust, Stewart; Langford‐Smith, Kia; Weisberg, Daniel; Canal, Maria; Breen, Catherine; Hepburn, Michelle; Tylee, Karen; Vaz, Frédéric M.; Vail, Andy; Wijburg, Frits; O'Leary, Claire; et al.
Abstract: The aim of this study was to evaluate the efficacy of high dose genistein aglycone in Sanfilippo syndrome (mucopolysaccharidosis type III). High doses of genistein aglycone have been shown to correct neuropathology and hyperactive behaviour in mice, but efficacy in humans is uncertain. This was a single centre, double‐blinded, randomised, placebo‐controlled study with open‐label extension phase. Randomised participants received either 160 mg/kg/day genistein aglycone or placebo for 12 months; subsequently all participants received genistein for 12 months. The primary outcome measure was the change in heparan sulfate concentration in cerebrospinal fluid (CSF), with secondary outcome measures including heparan sulfate in plasma and urine, total glycosaminoglycans in urine, cognitive and adaptive behaviour scores, quality of life measures and actigraphy. Twenty‐one participants were randomised and 20 completed the placebo‐controlled phase. After 12 months of treatment, the CSF heparan sulfate concentration was 5.5% lower in the genistein group (adjusted for baseline values), but this was not statistically significant ( P  = .26), and CSF heparan sulfate increased in both groups during the open‐label extension phase. Reduction of urinary glycosaminoglycans was significantly greater in the genistein group (32.1% lower than placebo after 12 months, P  = .0495). Other biochemical and clinical parameters showed no significant differences between groups. High dose genistein aglycone (160 mg/kg/day) was not associated with clinically meaningful reductions in CSF heparan sulfate and no evidence of clinical efficacy was detected. However, there was a statistically significant reduction in urine glycosaminoglycans. These data do not support the use of genistein aglycone therapy in mucopolysaccharidosis type III. High dose genistein aglycone does not lead to clinically meaningful reductions in biomarkers or improvement in neuropsychological outcomes in mucopolysaccharidosis type III.